Menemukan Kedamaian Hati di Tengah Riuhnya FOMO dan Media Sosial Melalui Mindfulness dan Hubungan Emosional yang Sejati - Muhammad Daffa Yuwan Syauqillah; Muamar Adnan Agassi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
The rapid expansion of social media has intensified the phenomenon of Fear of Missing Out (FOMO), a form of anxiety arising from the perception that others are experiencing more rewarding lives. With more than 5.17 billion active social media users worldwide in 2024, including Indonesians who spend over three hours daily on social media, FOMO has become an increasingly prevalent psychological and social issue. This study employs a qualitative approach using a systematic literature review to examine the relationship between social media use, FOMO, and psychological well-being, while exploring its spiritual dimensions from an Islamic perspective. The analysis draws on Social Comparison Theory, Self-Determination Theory, and Islamic psychospiritual concepts, particularly qana'ah (contentment) as articulated by Ibn Qayyim al-Jawziyyah. The findings indicate that FOMO is strongly influenced by social comparison, declining self-esteem, and compulsive engagement with digital platforms, all of which contradict Islamic values such as qana'ah, tawakkul (reliance on God), shukr (gratitude), and zuhd (detachment from excessive worldly attachment). The study argues that FOMO should be understood not only as a psychological problem but also as a spiritual challenge resulting from the erosion of inner contentment. To address this issue, the study proposes integrating evidence-based digital well-being strategies with Islamic spiritual practices, including mindful dhikr, structured digital detox, and gratitude cultivation. This research contributes to the growing field of Islamic digital psychology by offering an integrative framework for promoting psychological resilience and spiritual well-being in Muslim communities.